Sharpening Creativity in Elementary Education through Simple Fine Arts: Literature Review - Dwi Ambarsari, Yuliani; Azidan Alanthony, Muhammad; Ayu Safitri, Elisa; Muzdalifah, Syafina; Shahibatun Wafa, Najwa (UIN Raden Mas Said Surakarta, 2024)
Simple fine arts can be an effective and fun way to hone children’s creativity at the elementary school level. By allowing children to express themselves artistically, schools can strengthen their learning experiences and prepare them for broader future challenges. This research aims to explore the influence of simple visual arts on increasing the creativity of elementary/MI children through a Systematic Literature Review with the steps: developing the research question (formulating research questions), developing the search strategy (searching for articles or literature that match the research theme), selection criteria (applying inclusion criteria to select articles), evaluation and analysis data (evaluating and analyzing data), and interpreting (reporting research findings). A total of 22 articles were found that met the inclusion criteria for analysis. The research results show that fine arts can stimulate imagination and self-expression, develop fine motor skills, strengthen observation and concentration abilities, increase self-confidence and intrinsic motivation, and use simple materials for creative activities. Therefore, simple fine arts can be an effective means of developing children’s creativity at the elementary school level, so it is necessary to integrate art into the educational curriculum to improve children’s creative abilities